2007
DOI: 10.1016/j.vetmic.2006.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Use of quantitative real-time PCR to monitor the shedding and treatment of chlamydiae in the koala (Phascolarctos cinereus)

Abstract: The aim of this study was to monitor chlamydial shedding patterns in clinically affected koalas before, during and following treatment using quantitative real-time PCR. Swab samples were obtained from 14 koalas presented for treatment at the Australian Wildlife Hospital. Four of these animals were followed over a period of 8-9 weeks. Primers were designed based on the consensus signature sequence of the 16S rRNA chlamydial gene. Additional primers were designed based on the sequence of the koala beta-actin gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 20 publications
2
34
1
Order By: Relevance
“…Koalas are infected with two species of Chlamydia , C. pecorum and C. pneumoniae 1 , with C. pecorum being the primary pathogen, causing keratoconjunctivitis, reproductive disease, and even death (Fig. 1) 2 . An interesting aspect of koala disease ecology is that the degree of chlamydial virulence varies considerably within and between wild populations.…”
Section: Introductionmentioning
confidence: 99%
“…Koalas are infected with two species of Chlamydia , C. pecorum and C. pneumoniae 1 , with C. pecorum being the primary pathogen, causing keratoconjunctivitis, reproductive disease, and even death (Fig. 1) 2 . An interesting aspect of koala disease ecology is that the degree of chlamydial virulence varies considerably within and between wild populations.…”
Section: Introductionmentioning
confidence: 99%
“…This decline has mostly been attributed to habitat fragmentation (Martin and Handasyde 1999) and loss through clearing for agriculture and urban development (Cogger et al 2003;Sullivan et al 2004;Gordon et al 2006;Lane 2008;DERM 2009). Recently, an important role has been suggested for disease in the decline of koala populations, with chlamydial infection being implicated as the primary cause of disease (Timms 2005;Markey et al 2007;Higgins 2008). Exacerbation of the disease may be attributed to the koala retrovirus (Tarlinton et al 2005) and stress from habitat clearing and other anthropogenic impacts (Weigler et al 1988;Lee et al 2010;Brearley et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Such individuals may continue to shed DNA while harboring nonviable organisms after starting treatment (1,23,38). This time period appears to correlate with drug effectiveness not only for reaching the infected area but also for inactivating bacteria (1,23,38). Some organisms are able to withstand and shield themselves from treatment better than others, and slowgrowing mycobacteria are among the most difficult to target.…”
Section: Discussionmentioning
confidence: 99%
“…Some organisms are able to withstand and shield themselves from treatment better than others, and slowgrowing mycobacteria are among the most difficult to target. For example, studies have shown that leprosy patients (with M. leprae disease) continue to test positive by PCR 3 months posttreatment compared to patients diagnosed with infections by chlamydia, whose DNA is no longer detected after the second week of treatment (23,38).…”
Section: Discussionmentioning
confidence: 99%